Design, construction, and control of a 3d printed Diwheel prototype (2024)
This project extends beyond the successful realization of a 3D-printed Diwheel prototype by meticulously guiding the process from concept to completion. The initial stages involved a thorough review of existing Diwheel designs and the application of modular 3D printing techniques, culminating in the creation of a fully functional prototype. By employing advanced system identification methods, a dynamic model was developed to accurately represent the behavior of the Diwheel. This model enabled the implementation of control strategies, ensuring stable and responsive operation across various conditions, demonstrating the effectiveness of the design and control techniques.